Put your eyes up here and other school poems - Dakos, Kalli; Karas, G. Brian (New York : Aladdin Paperbacks, 2006)
A collection of humorous and poignant poems chronicling the school year in Ms. Roys's fourth-grade class.
Wilson's Children, October 2006
School Library Journal, July 2003
Publisher's Weekly, August 2003
Booklist, August 2003
Horn Book, April 2004
Kirkus Review, July 2003
Keywords: Teacher-student relationships -- Juvenile poetry; Fourth grade (Education) -- Juvenile poetry; Primary school teachers -- Juvenile poetry; School children -- Juvenile poetry; Children's poetry, American; Teacher-student relationships -- Poetry; Teachers -- Poetry; Students -- Poetry; Schools -- Poetry; American poetry; Teacher-student relationship -- Poetry; Teachers -- Poetry; Students -- Poetry; Schools -- Poetry; American poetry